"HISTOIRE DE LA TRADUCTION LITTÉRAIRE EN EUROPE MÉDIANE" – BOOK PRESENTATION: “TRANSLATORS ARE THE REAL EUROPEANS.” (KONRÁD GYÖRGY, 2007) - WALCZ, Beatrix (Studia Universitatis Babeș-Bolyai Philologia, 2019)
On 27th of November 2019 in Budapest it was held a presentation of the French book entitled The History of Literary Translation in “Median Europe”. This book was aimed to make a synthesis about the translation culture of this place, that can be interpreted as geopolitically, but also as a culturally determined area. Geographically it can be described as a collection of the countries situated between the German and the eastern Slavic countries. On the respective book there had been working 26 researchers speaking 16 languages: Albanian, Bosnian-Croatian-Serbian, Bulgarian, Estonian, Finnish, Hungarian, Lettish, Lithuanian, Macedonian, Polish, Romanian, Slovak, Slovenian, Sorbian, Czech and Ukrainian. The book appeared in this year in Paris, in French language, as a result of a ten-year long collaboration between researchers and editors.